2017
DOI: 10.1111/bcpt.12838
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Reliability of Halothane‐anaesthetized Microminipigs to Assess Risk of Drug‐induced Long QT Syndrome

Abstract: Using moxifloxacin and terfenadine, which are known to induce benign and malignant QT interval prolongation, respectively, we analysed whether halothane-anaesthetized microminipigs are an appropriate model for assessing the risk of drug-induced long QT syndrome. Moxifloxacin (0.03, 0.3 and 3 mg/kg) and terfenadine (0.03, 0.3 and 3 mg/kg) were intravenously infused over 10 min. with a pause of 20 min. to the halothane-anaesthetized microminipigs (n = 4 for each drug). Moxifloxacin decreased the heart rate, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Namely, we assessed the effects of pilsicainide, verapamil and E-4031 on microminipigs, which preferentially suppress Na + , Ca 2+ and K + channels, respectively (Matsukura et al, 2017); those of dl-sotalol, which can block both ß adrenoceptor and K + channel (Yokoyama et al, 2017); and those of moxifloxacin and terfenadine, which inhibit various cardiac ionic channels, leading to benign and malignant QT-interval prolongation, respectively . We have also compared those with the beagle dogs in our previous studies using the same experimental conditions, and shown that microminipigs may have smaller effective volume of drug distribution; greater basal sympathetic tone resulting in lessened hypotension-induced, reflex-mediated increase of sympathetic tone; and/or smaller repolarization reserve than beagle dogs (Cao et al, 2017;Matsukura et al, 2017;Yokoyama et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, we assessed the effects of pilsicainide, verapamil and E-4031 on microminipigs, which preferentially suppress Na + , Ca 2+ and K + channels, respectively (Matsukura et al, 2017); those of dl-sotalol, which can block both ß adrenoceptor and K + channel (Yokoyama et al, 2017); and those of moxifloxacin and terfenadine, which inhibit various cardiac ionic channels, leading to benign and malignant QT-interval prolongation, respectively . We have also compared those with the beagle dogs in our previous studies using the same experimental conditions, and shown that microminipigs may have smaller effective volume of drug distribution; greater basal sympathetic tone resulting in lessened hypotension-induced, reflex-mediated increase of sympathetic tone; and/or smaller repolarization reserve than beagle dogs (Cao et al, 2017;Matsukura et al, 2017;Yokoyama et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Microminipigs are extraordinarily small-sized miniature pigs, weighing approximately 7 kg at 6 months of age when they mature, which were developed by Fuji Micra Inc. (Shizuoka, Japan) (Kaneko et al, 2011). We have pharmacologically characterized microminipig as an in vivo laboratory animal for safety pharmacology study under halothane-anesthesia using several typical cardiac ion channel and receptor modulators (Cao et al, 2017;Matsukura et al, 2017;Yokoyama et al, 2017). Namely, we assessed the effects of pilsicainide, verapamil and E-4031 on microminipigs, which preferentially suppress Na + , Ca 2+ and K + channels, respectively (Matsukura et al, 2017); those of dl-sotalol, which can block both ß adrenoceptor and K + channel (Yokoyama et al, 2017); and those of moxifloxacin and terfenadine, which inhibit various cardiac ionic channels, leading to benign and malignant QT-interval prolongation, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Microminipig is an extraordinarily small-sized miniature pig, which has been characterized as an alternative in vivo experimental model animal to dogs and monkeys for life science research including pharmacological and toxicological studies [1, 3, 5, 7-11, 16, 18]. Although electropharmacological studies have been extensively performed using the halothane-anesthetized microminipig [1, 3,5,9,10,16,18], it is still unknown how much the conventional correction formulae described above can attenuate the heart rate-dependent impacts on the QT interval of microminipig and how much difference is present in the amount of ventricular IKs current among microminipigs, humans and dogs. In order to answer such questions, we tried to develop correction formulae for microminipigs by adopting atrial electrical pacing protocol, which were compared with the conventional ones for humans and dogs [13].…”
mentioning
confidence: 99%
“…The current correction formulae were developed by using the data obtained from 5 male microminipigs, the number of which might be too small to apply these formulae to the global population of microminipigs. Accordingly, we assessed whether the new correction formulae could properly correct the QT interval by using previously obtained experimental results of the heart rate and QT interval from 42 male and 11 female micominipigs [1, 3,5,9,10,16,18]. The new correction formulae made the slope of regression lines for the QT interval of total, male and female micominipigs more flat, as shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation